Dynamic Maxillary Sinus Changes of Facial Vascularized Composite Allotransplants. Issue 3 (23rd February 2021) - Kauke, Martin; Safi, Ali-Farid; Palmer, William Jackson; Kollar, Branislav; Nelms, Laurel; Tchiloemba, Bianief; Haug, Valentin; Pomahac, Bohdan
Abstract : Summary: Skin is one of the target tissues of rejection in face transplants and, because of its easy accessibility, has become the gold standard in the diagnosis of rejection. The allograft contains deeper tissues where rejection can occur, but samples cannot be obtained because of difficult access. Deep tissue changes were monitored on computed tomographic scans of the midface in six face transplant recipients with the help of image segmentation. The maxillary sinus was identified as a dynamic anatomical compartment. Observed changes in volume of the aeration relative to the opacification (aeration coefficient) of the maxillary sinus were quantified with the help of image segmentation. Changes in the aeration coefficient as a surrogate of mucosal swelling were quantified and related to time, treatment, and skin rejection grade. Lower aeration coefficients were found only in patients with transplanted maxillary sinus mucosa. Pathologic changes were not observed in face transplant recipients with a native maxillary sinus. The data show that the aeration coefficient was significantly lower at the time of biopsy-proven allograft rejection. Neither mechanical, nor infectious, nor medication side effects sufficiently explain the findings presented herein. The authors' findings are important to consider for clinical management of face transplant patients who receive parts of the sinonasal tract. The authors identify a potential radiologic biomarker of deep tissue allograft rejection. In the future, the proposed methodology might prove useful in monitoring deeper dynamic tissue changes in vascularized composite allografts and might help in designing patient-specific, individualized treatment strategies.